White Pass & Yukon Railroad station and warehouses, summit of White Pass, Alaska, April 9, 1899. - Hegg, Eric A., 1867-1948 (1899)
Caption on image: "Ware houses on the summit on White Pass and Yukon Route April 9th '99" Original image in Hegg Album 2, page 43. Original photograph by Eric A. Hegg 676; copied by Webster and Stevens 295.A